PEMBERDAYAAN MASYARAKAT MELALUI EDUKASI PEMANFAATAN LIMBAH RUMAH TANGGA DENGAN METODE TAKAKURA DI DESA ILOHELUMA KABUPATEN BONE BOLANGO - Apriliani, Silvana; R, St. Aisyah; Sirajuddin, Zulham; Azis, Muhammad Arief; Lamatenggo, Rezka; Manopo, Suslara Santika (Universitas Mataram, 2024)
The Takakura method is a sustainable small-scale composting technique. The issue faced by the Iloheluma Village community is a lack of skills in managing household waste, leading to improper waste disposal, environmental pollution, and waste accumulation that degrades the village’s appearance. This community service activity aimed to enhance the community's understanding and skills in effectively managing household waste using the Takakura method. The activities involved observation, coordination, waste management counseling, and hands-on training. The results demonstrated an increase in the community's ability to manage waste, reduce waste accumulation, and raise awareness of proper waste management practices.